THE MATHEMATICAL DESCRIPTION OF PROCESS OF FORMATION OF GEOMETRICAL PARAMETERS OF THE SUPERFICIAL LAYER AND HARDENING AT PROCESSING DETAILS IN FRACTION - V.G. Lebedenko (Advanced Engineering Research)
The system of theoretical models past experimental check is developed. The given models can be used for increase of efficiency of strengthening processing in fraction at a stage of technological designing